National Survey of Smoking and Smoking Cessation Education Within UK Midwifery School Curricula. Issue 5 (11th April 2017) - Forman, Jane; Harris, James M.; Lorencatto, Fabiana; McEwen, Andy; Duaso, Maria J.
Abstract: Introduction: Smoking in pregnancy in the United Kingdom remains prevalent (11%). To encourage and support pregnant smokers to quit, midwives must be adequately trained to do so. Substantial curricular gaps have been identified in the smoking cessation training of medical, nursing, and optometry schools. This study aimed to identify the extent of smoking cessation training and assessment in UK midwifery schools. Methods: All UK undergraduate midwifery schools ( n = 53) were invited to complete a web-based survey of their curricular coverage and assessment related to smoking cessation, and perceived barriers to delivering smoking cessation training. Results: Twenty-nine (55%) midwifery schools responded. Most teaching was completed in the initial year of study. All reported teaching the harmful effects of tobacco use. The majority of respondents (83%) reported training students in brief intervention delivery and ways to assist quit attempts. Only 24% of schools in this study included relapse prevention in their curriculum. The most frequently reported barriers to teaching smoking cessation were "lack of knowledge amongst staff" (17%), "no space in a crowded curriculum" (17%), and "administrative problems" (13%). Conclusions: Midwifery schools are teaching the harmful effects of smoking and providing training on brief interventions. However, in some schools student midwives are not being sufficiently trained on relapse prevention or assessed in the practical skills necessary for delivering evidence-based interventions. Implications: Midwifery schools should revise the content and delivery of smoking cessation training to ensure midwives are equipped with the necessary knowledge and skills to contribute to the challenge of smoking cessation in pregnancy.